상상력의 자유로운 놀이와 개념 규칙의 규범성 - 신창화; Shin Chang Hwa (칸트연구, 2024)
본 논문은 상상력이 개념에 의해 부여된 규칙을 위반할 수 있다는 점에서 ‘놀이’의 능력임을 보이고자 한다. 이러한 목적에 따라 상상력이 개념 규칙을 위반하는 사례를 『실용적 관점에서 본 인간학』에서 찾아 고찰하고, 상상력이 범주로부터 독립해 있지는 않지만 경험적 개별 개념에는 종속되지 않는 방식으로 작동한다는 점을 보이고자 한다. 그리고 이 주장에 근거하여 『판단력비판』에 등장하는 “상상력의 자유로운 놀이” 개념을 해설해 보고자 한다. 이러한 본 논문의 작업은 긴스보그의 칸트 해석에 대한 비판적 평가를 경유하여 수행될 것이다. 칸트는 『인간학』과 『판단력비판』에서 공히 상상력이 자유로운 놀이를 하면서도 합법칙적인 능력이라고 서술하는데, 이러한 서술은 상상력이 규칙의 능력으로서 지성의 관할에서 벗어나 있으면서도 그것에 따른다고 하는 일견 모순적인 서술로 읽힐 수 있다. 긴스보그는 1997년 논문에서 이러한 문제의식에 따라, 상상력이 지성의 규칙에 의해 인도된다고 하는 규범주의적 모델과 상상력이 개념에 의해 인도되지는 않고 단순히 맹목적인 규칙성만을 가진다고 하는 자연주의적 모델을 모두 거부한다. 긴스보그는 이 두 모델을 모두 거부하고 자신의 독창적인 견해, 즉 상상력에는 규칙을 따르려고 하는 암묵적이고 원초적인 성향이 내재되어 있고, 그것이 발현되어 명시화된 결과 비로소 개념이 성립하게 된다는 입장을 내어놓게 된다. 본 논문은 이러한 긴스보그의 입장에 따라서는 상상력이 개념을 위반하는 칸트의 서술들을 설명하기 어렵다는 난점에 따라 긴스보그의 원초적 규범성 이론을 반박하고, 긴스보그가 거부한 바 있었던 규범주의적 모델 중 범주 인도 모델을 지지하고자 한다. 이에 따라 2장에서는 긴스보그의 1997년 논문을 상세하게 분석하고, 3장에서는 긴스보그의 모델이 가지는 문제점들을 지적하도록 하겠다. 나아가 4장에서는 어떻게 상상력이 개념-규칙을 내재적인 작동 원리로 포함하지 않으면서도 작동할 수 있는지를 『순수이성비판』「선험적 연역」에 등장한 “형상적 종합”을 통해 제시할 것이며, 이러한 주장이 가질 수 있는 가능한 문제를 다루며 논의를 마무리하겠다. This paper aims to demonstrate that imagination is the ability to “play” in the sense that it can violate the rules imposed by concepts. With this objective in mind, examples of imagination violating conceptual rules are examined in Anthropology from a Pragmatic Point of View, to show that although imagination is not independent of categories, it operates independently from empirical particular concepts. Additionally, based on this assertion, the concept of “free play of imagination” appearing in Critique of Judgment is interpreted. This work is conducted by critically evaluating Ginsborg’s interpretation of Kant, particularly regarding the notion of imagination. Kant, in both Anthropology and Critique of Judgment, describes imagination as engaging in a free play while still being a lawful faculty, which could be regarded as seemingly contradictory statements, suggesting that imagination is free from the regulation of understanding while still adhering to it. In response to this problematic aspect, Ginsborg, in her 1997 paper, rejects both the “normative model” where imagination is led by the rules of understanding, and the “naturalistic model” where imagination is not led by concepts but simply possesses blind regularity. She rejects both models and proposes her original view that imagination inherently has a disposition to follow rules implicitly, and only when it is explicitly manifested and reflected does concepts occur. This paper aims to refute her theory of primitive normativity, arguing that according to her standpoint, it is hard to explain Kant’s descriptions of imagination violating concepts. Instead, I support the “hybrid model” that she refuted in her 1997 paper. Accordingly, Chapter 2 provides a detailed analysis of her 1997 paper, while Chapter 3 points out the problems inherent in her model. Furthermore, including concepts/rules, through “figurative synthesis” mentioned in the “Transcendental Deduction” of Critique of Pure Reason, addressing possible issues arising from this argument and concluding the discussion.